Apoptosis resistance of nonobese diabetic peripheral lymphocytes linked to the Idd5 diabetes susceptibility region - Colucci, Francesco (The National Academy of Sciences of the USA, 1997)
Defects in lymphocyte apoptosis may lead to autoimmune disorders and contribute to the pathogenesis of type 1 diabetes. Lymphocytes of nonobese diabetic (NOD) mice, an animal model of autoimmune diabetes, have been found resistant to various apoptosis signals, including the alkylating drug cyclophosphamide. Using an F(2) intercross between the apoptosis-resistant NOD mouse and the apoptosis-susceptible C57BL/6 mouse, we define a major locus controlling the apoptosis-resistance phenotype and demonstrate its linkage (logarithm of odds score = 3.9) to a group of medial markers on chromosome 1. The newly defined gene cannot be dissociated from Ctla4 and Cd28 and in fact marks a 20-centimorgan region encompassing Idd5, a previously postulated diabetes susceptibility locus. Interestingly, we find that the CTLA-4 (cytotoxic T lymphocyte-associated antigen 4) and the CD28 costimulatory molecules are defectively expressed in NOD mice, suggesting that one or both of these molecules may be involved in the control of apoptosis resistance and, in turn, in diabetes susceptibility.